2020
DOI: 10.1038/s41598-020-78883-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fatty pancreas and hypertriglyceridemic waist phenotype: a cross-sectional study

Abstract: Hypertriglyceridemic waist phenotype (HTWP) and its quantitative indicator, waist circumference-triglyceride index (WTI), are common quantitative indices of visceral obesity and are closely related to metabolic diseases. The purpose of this study was to investigate the relationship between fatty pancreas (FP) and HTWP in China. FP was diagnosed using trans-abdominal ultrasonography in all participants. According to the waist circumference and serum triglyceride levels, the participants were divided into four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, Jaghutriz et al 31 who assessed the metabolomic characteristics of fatty pancreas in prediabetics identified as association between NAFPD and obesity. Also, Sotoudehmanesh et al 29 and Yu et al 32 found an association between NAFPD and dyslipidemia. Furthermore, Chiyanika et al 34 reported a significant association between NAFPD and MetS in obese adolescents.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Jaghutriz et al 31 who assessed the metabolomic characteristics of fatty pancreas in prediabetics identified as association between NAFPD and obesity. Also, Sotoudehmanesh et al 29 and Yu et al 32 found an association between NAFPD and dyslipidemia. Furthermore, Chiyanika et al 34 reported a significant association between NAFPD and MetS in obese adolescents.…”
Section: Discussionmentioning
confidence: 94%
“…The limitations of our study are its single center and retrospective study design, and that there were no differences in BMI and obesity between the two groups, despite the fact that fatty pancreas was shown to be associated with obesity, mainly central visceral obesity, and hypertriglyceridemia [35]. In our study, we had data regarding BMI and obesity in general but not concerning central obesity, and this is likely to have contributed to the similar rate of obesity we recorded between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Another study also reported that the HTGW phenotype was associated with systemic inflammatory response syndrome, organ failure and severity of AP. 31 In addition, there is research showing that the HTGW phenotype is closely related to fatty pancreas, 32 suggesting that visceral obesity and fatty pancreas may be related to AP in some way. There are several hypotheses that can explain the correlation between the HTGW phenotype, and the incidence of AP.…”
Section: Discussionmentioning
confidence: 99%